Influence of shear rate and temperature on the dynamic viscosity of a polymer solution - Nakhai, Дмитрий Михайлович; Mikanovich, Дмитрий Станиславович; Busel, Михаил Олегович (Journal of Civil Protection, 2023)
Purpose. Study of the features of changes in the dynamic viscosity of non-Newtonian fluids due to changes in the velocity gradient (shear rate) gradient and temperature. Methods. The viscosity of the solutions was measured on an IKA ROTAVISC LO-VI rotational viscometer. An FT-316-40 liquid cryothermostat was used to measure the temperature of the studied solutions. The addition of the required amount of the test liquid was carried out using a Thermo Fischer Scientific pipette dispenser. Findings. According to the results of a detailed analysis of the dependence of the properties of polymeric (non-Newtonian) liquids on the percentage of surface active substances in the solution (from 0.1 to 3 %), the degree of heating of the studied liquids (from 5 to 35 ºС) and the velocity gradient (shear rate 1.28–259.13 s-1), the features of the change in dynamic viscosity were established, indicating the presence of a near-wall effect. Application field of research. The results obtained are important for further investigation of the behavior of polymeric (non-Newtonian) fluids used in industrial facilities.